2021
DOI: 10.1111/cbdd.13905
|View full text |Cite
|
Sign up to set email alerts
|

Phthalimide‐(N‐alkylbenzylamine) cysteamide hybrids as multifunctional agents against Alzheimer’s disease: Design, synthesis, and biological evaluation

Abstract: The complex pathogenesis of Alzheimer's disease (AD) calls for multi-target approach for disease treatment. Herein, based on the MTDLs strategy, a series of phthalimide-(N-alkylbenzylamine) cysteamide hybrids were designed, synthesized, and investigated in vitro for the purpose. Most of the target compounds were found to be potential multi-target agents. In vitro results showed that compound 9e was the representative compound in this series, endowed with high EeAChE and HuAChE inhibitory potency (IC 50 = 1.55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The phthalimide and its derivatives have often been used as fungicidal components for control of fungal diseases for crop production [38,39], and the intermediate derivatives such as tetramethrin, phosmet, and dialifos have been used as insecticides for control of insect pests [11]. Therefore, it is speculated that the phthalimide derivatives 4a, 4c, and 4d, may have possessed similar structures, such as the phthalimide pharmacophore (Figure 1), which might play an important role in contributing to insecticidal activities, such as binding to cholinesterase enzymes with inhibitory effect on target insect pests [9,10]. The derivatives 4a, 4c, and 4d showed potential to control tephritid fruit flies, such as the Caribbean fruit fly, A. suspensa, which has been an important insect pest for subtropical fruit crops in south Florida.…”
Section: Toxicity To the Caribbean Fruit Flymentioning
confidence: 99%
See 1 more Smart Citation
“…The phthalimide and its derivatives have often been used as fungicidal components for control of fungal diseases for crop production [38,39], and the intermediate derivatives such as tetramethrin, phosmet, and dialifos have been used as insecticides for control of insect pests [11]. Therefore, it is speculated that the phthalimide derivatives 4a, 4c, and 4d, may have possessed similar structures, such as the phthalimide pharmacophore (Figure 1), which might play an important role in contributing to insecticidal activities, such as binding to cholinesterase enzymes with inhibitory effect on target insect pests [9,10]. The derivatives 4a, 4c, and 4d showed potential to control tephritid fruit flies, such as the Caribbean fruit fly, A. suspensa, which has been an important insect pest for subtropical fruit crops in south Florida.…”
Section: Toxicity To the Caribbean Fruit Flymentioning
confidence: 99%
“…The minimum inhibitory concentrations (MICs) values of cyclic imide structures could be comparable to clinically used antibiotics [8]. Panek et al and Zhang et al have shown in different studies that the phthalimide structure plays an important role in binding to cholinesterase enzymes and showing inhibitory activity [9,10], which is one of the key mechanisms for pest control. Therefore, compounds with phthalimide structure are likely to bind to cholinesterase enzymes of insects and exhibit inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease in short AD is a progressive age‐related neurodegenerative brain disease characterized by gradual loss of memory and other cognitive functions (Heng Zhang et al, 2021; Honghua Zhang et al, 2022; Singh et al, 2020; Singh, Rai et al, 2021; Yuxi He et al, 2021). AD was first discovered in 1906 by the German clinical psychiatrist and neuroanatomist Alos Alzheimer in the brain of a 50‐year‐old lady (Sang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%